Implementasi Strategi Konstruktivistik dalam Pembelajaran Bahasa Arab untuk Meningkatkan Minat Belajar Siswa - Hardian Hardian; Aminudin Aminudin (Jurnal Eduslamic, 2026)
This study aims to analyze the implementation of constructivist strategies in Arabic language learning to enhance students’ learning interest at Madrasah Aliyah Al-Hariri Tebo Ilir. The study employed a qualitative approach using a descriptive case study design to obtain an in-depth understanding of the learning process within the natural context of Islamic boarding school education. The research subjects consisted of 12 informants, including one Arabic language teacher, eight tenth-grade students, and three school management representatives selected purposively based on their involvement in the learning process. Data were collected through participatory observation, semi-structured interviews, and documentation, then analyzed using the interactive model of Miles and Huberman involving data reduction, data display, and conclusion drawing. The findings revealed that the implementation of constructivist learning strategies was carried out through several approaches, including providing initial motivation, presenting interesting learning materials, applying varied learning methods, utilizing learning media, and conducting continuous evaluation. These strategies succeeded in creating active, contextual, and student-centered learning experiences that increased students’ feelings of enjoyment, interest, attention, and active involvement in Arabic learning.